1983
DOI: 10.1530/jrf.0.0670373
|View full text |Cite
|
Sign up to set email alerts
|

Changes in prostaglandin levels in the sensitized and non-sensitized uterus of the mouse after the intrauterine instillation of oil or saline

Abstract: Intrauterine instillation of oil, but not saline, induced both a decidual cell reaction and a marked elevation in the uterine PGF-alpha content of suitably sensitized ovariectomized mice. Uterine PGF-alpha concentrations were elevated within 5 min of the oil instillation, reached maximal levels within 30-60 min and then declined to near baseline levels again by 3 h. A similar increase in uterine PGF-alpha content in response to oil instillation was seen in non-sensitized females, although no decidual cell reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…For mice, there are varying reports for the effects of deciduogenic stimuli. Jonsson et al (1979), Rankin et al (1979) and Milligan & Lytton (1983) all found the PGF 2a concentrations to be rapidly increased after stimulation. Jonsson et al (1979) reported that PGE 2 was also increased, while Milligan & Lytton (1983) found PGE 2 as well as PGI 2 to be unchanged.…”
Section: Which Pg?mentioning
confidence: 87%
“…For mice, there are varying reports for the effects of deciduogenic stimuli. Jonsson et al (1979), Rankin et al (1979) and Milligan & Lytton (1983) all found the PGF 2a concentrations to be rapidly increased after stimulation. Jonsson et al (1979) reported that PGE 2 was also increased, while Milligan & Lytton (1983) found PGE 2 as well as PGI 2 to be unchanged.…”
Section: Which Pg?mentioning
confidence: 87%
“…3). Prostaglandins and cyclic AMP have been strongly implicated as potential mediators of these responses, but their precise role is still unclear (Milligan & Lytton, 1983;Kennedy, 1984). To what extent the transient period of hormone-induced sensitivity to deciduogenic stimuli is dependent on qualitative and/or quantita¬ tive changes in the production of (Kennedy, 1983), or sensitivity to (Kennedy et ai, 1983), such stimuli remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Not all data are in agreement; in the hamster, prostaglandins E, but not F, concentrations are elevated at implantation sites (Evans and Kennedy 1978) while in the mouse, uterine concentrations of prostaglandins F, but not E or 12, are elevated in response to a deciduogenic stimulus (Milligan and Lytton 1983). Thus measurements of prostaglandins have not identified a single prostaglandin as the mediator of the endometrial vascular changes.…”
Section: Which Prostaglandins?mentioning
confidence: 96%
“…In addition, oestrogens in low dosages act synergistically with progesterone to sensitize the rat and mouse uterus for the decidual cell reaction (Yochim and De Feo 1963;Armstrong and King 1971;Finn and Porter 1975). That these changes in uterine sensitization might be related to the ability of the uterus to produce prostaglandins has been investigated but the results indicate that uterine prostaglandin levels in response to a standardized artificial stimulus does not provide a ready explanation for the changes in sensitization (Kennedy 1980a(Kennedy , 1980bMilligan and Lytton 1983). Rather, maximum uterine sensitization corresponded with the maximum ability of the endometrium to respond to intrauterine-injected prostaglandin E2 with increased endometrial vascular permeability (Kennedy 1980a(Kennedy , 1980b.…”
Section: Control Of Uterine Sensitizationmentioning
confidence: 99%